Polityka agrarna rządu Władysława Grabskiego w latach 1923-1925 - Chylak, Karol (Acta Universitatis Lodziensis. Folia Historica, 2005)
After the First World War the Republic of Poland was an agricultural country where almost 2/3 of the population of a country was cultivating. This agrarian structure, with dwarf farms, was not very profitable, because it did not give maintenance to its owner, and it had no prospects of development for the future. The most important issues were the remains of archaic ways of farming such as patchwork and land communities. Poland was not raised from the dead yet when the issue of the agrarian reforms divided politicians into two hostile camps. This state of the situation had disastrous influence on reformist conceptions because some parties had more and more radical watchwords and the other ones were falling into extreme conservatism. As a result of such conduct there was the establishment of agrarian relations. On 10th July, 1919 the Seym (the lower house of the Polish Parliament) adopted a resolution concerning the agricultural reform and on 15th July, 1920 following it a bill, which were both the result of the compromise. None of political options was satisfied of that bill, so nobody cared deeply about the realization of the bill. Władysław Grabski did not have to be concerned about the demands of the agricultural reform which were becoming more and more radical. The tension round the issue was his own fault, the consequence of the adoption of the tactic to find support in the Seym. The Prime Minister did not have any uniform, reformist manifesto. He was selecting his associates on the basis of the profit or the loss of votes in Parliament, not taking the realization of the bill into consideration. In the first half ol 1924, when the highest positions were taken by the people of the Right, Władysław Grabski was realizing the conception of the transformation of the agrarian structure using economic stimuli. Bigger properties were due to be taxed. At the same time some preparations were made to introduce State Agricultural Bank whose aim was to help in integrating of farmlands. To meet with support in Parliament Władysław Grabski resigned as Minister of Agricultural Reforms. W. Kopczyński, the candidate of the Polish Peasant Party „Liberation" was Władysław Grabski’s successor. It was unavoidable to introduce the issue of the agricultural reform in forum of the Seym where politics were more important than sober thinking. It was failure of reforms connected with the Polish country because politics once again won with a Polish raison d’etat.